The gentle pressure of the sky - Watermeyer, Laura (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2015)
A collection of lyrical, imaginative prose, ranging from prose poems to more formal short stories to flash fiction. I challenge the ordinary or commonplace by exploring the realms between fiction and poetry, realism and fantasy, reality and illusion. I would like reading the collection to be a sensory experience, one that draws the reader deeper into the imaginary. Stylistically, I work elements of poetic language into the narrative in order to express the mystery and remoteness that the stories require.
Keywords: South African fiction (English) -- 21st century; South African fiction (English) -- Study and teaching (Higher); South African poetry (English) -- Study and teaching (Higher); Creative writing (Higher education) -- South Africa; Short stories, South African -- 21st century